Pengembangan Media Hologram Berbasis Fan Projection untuk Meningkatkan Minat Belajar Siswa Kelas VII - Fausan, Aswat Ahmad; Fakhrunnisaa, Nur (ISLAMIKA, 2025)
The research discusses the development of fan projection-based hologram media in increasing learning interest in class VII MTs N Palopo City. The research aims to determine the stages of media development, to find out whether it is valid or not in increasing students' learning interest in prayer procedures material. The research uses the R&D (Research and Development) type, and the ADDIE model stages: Analysis Design, Development, Implementation, Evaluation. Subject students in class VII.H MTs N Palopo City. This research uses data collection techniques by means of interviews, questionnaires and documentation. The data analysis used is qualitative and quantitative. The results of the research obtained validation results from media experts 93% "very valid", material experts 88% "very valid" and the level of student interest in learning obtained 73.3% "interested". Based on this, it was concluded that the development of fan projection-based holograms to increase interest in learning about prayer procedures material in class VII MTs N Palopo City could be used as a learning medium.